Manufacturing method of electrolytic copper foil

JP7607784B2Active Publication Date: 2024-12-27KOREA ZINC CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023544266
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-03-28
Publication Date
2024-12-27
Estimated Expiration
2043-03-28

AI Technical Summary

Benefits of technology

【0027】 開示された電解銅箔の製造方法によれば、電解銅箔の製造のための電解液に銅イオンとともにニッケルイオンを添加することによって電解銅箔のカールの特性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607784000001
    Figure 0007607784000001
  • Figure 0007607784000002
    Figure 0007607784000002
  • Figure 0007607784000003
    Figure 0007607784000003
Patent Text Reader

Abstract

A method for manufacturing an electrolytic copper foil according to an embodiment of the present invention includes the steps of dissolving copper (Cu) and nickel (Ni) in sulfuric acid to prepare an electrolyte solution containing copper ions and nickel ions, and providing a current to an anode plate and a cathode rotating drum spaced apart from each other in the electrolyte solution to provide a copper layer, and the concentration of the nickel ions is adjusted to 50 ppm to 350 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing electrolytic copper foil by placing an anode plate and a cathode rotating drum in an electrolyte containing copper ions and nickel ions and supplying an electric current. [Background technology]

[0002] A secondary battery is a type of energy conversion device that converts electrical energy into chemical energy, stores it, and then converts the chemical energy back into electrical energy when electricity is needed. Secondary batteries are also called rechargeable batteries because they can be recharged.

[0003] Among these secondary batteries, lithium secondary batteries have the characteristics of high operating voltage, high energy density, and excellent life. In recent years, the demand for lithium secondary batteries has been rapidly increasing due to the increased use of portable electronic devices such as smartphones and laptops, and the commercialization of electric vehicles. Such secondary batteries include a negative electrode current collector made of copper foil, and among copper foils, electrolytic copper foil is widely used as the negative electrode current collector of secondary batteries. As the demand for secondary batteries increases, the demand for high-capacity, high-efficiency, and high-quality secondary batteries increases, and copper foils that can improve the characteristics of secondary batteries are required. In particular, copper foils that can ensure high capacity and stable capacity maintenance of secondary batteries are required.

[0004] Recently, the manufacturing process of electrolytic copper foil is mainly done by the roll-to-roll method, which allows for mass production and has the advantage of being able to produce copper foil with a wide width and thin thickness. Recently, copper foil with a thickness of 10μm or less is required, and copper foil with a thickness of 8μm and 6μm is commonly used.

[0005] The thinner the copper foil, the more current collectors can be accommodated in the same space, which increases the capacity of the secondary battery. However, the thinner the copper foil, the more likely it is to curl, which can cause defects such as breakage or wrinkles during winding, making it difficult to manufacture a very thin film of copper foil. Therefore, in order to manufacture a very thin copper foil, it is necessary to prevent the copper foil from curling.

[0006] Considering this, it is necessary to prevent curling, wrinkling, or tearing of the copper foil not only in the manufacturing process of the copper foil but also in the manufacturing process of a secondary battery electrode or a secondary battery using the copper foil. In particular, in the manufacturing process of the copper foil or the electrode for a secondary battery using the copper foil by a roll-to-roll process, it is necessary to prevent defects such as tearing of the edge of the copper foil during the winding process or coating process of the active material.

[0007] In the past, in order to suppress the occurrence of curling in electrolytic copper foil, attempts were made to adjust the curling characteristics by adjusting the amount of organic compound-based additives added. For example, Patent Document 1 discloses a technology that uses saccharin as an organic compound to improve curling characteristics, and Patent Document 2 discloses a technology that adds a brightener containing an arsenic-containing metal salt to an electrolyte instead of an organic compound for adjusting physical properties to improve the curling characteristics of copper foil.

[0008] However, although the curl characteristics of copper foil can be adjusted by adding additives such as saccharin, this changes the basic physical properties of the copper foil, making process management difficult as the amount of additives used to adjust the properties must also be adjusted. Arsenic (As) exists as arsenous acid (H3AsO3) in acidic solutions, and arsenic acid is mainly used as a raw material for rodenticides and insecticides; it is highly toxic and requires careful handling.

[0009] In order to solve these problems, there is a need for a manufacturing technique for an electrodeposited copper foil that can easily control the curl characteristics of the electrodeposited copper foil without changing the amount of additives that control the physical properties of the electrodeposited copper foil. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent No. 10-0389061 [Patent Document 2] JP 2020-530878 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present disclosure aims to prevent defects such as breakage or wrinkles in electrolytic copper foil by preventing curling that may occur during the production process of electrolytic copper foil, and aims to provide a method for producing electrolytic copper foil that can prevent curling of electrolytic copper foil by adding nickel (Ni) ions to an electrolyte for producing electrolytic copper foil. [Means for solving the problem]

[0012] A method for manufacturing an electrolytic copper foil according to an embodiment of the present invention includes the steps of: dissolving copper (Cu) and nickel (Ni) in sulfuric acid to prepare an electrolyte solution containing copper ions and nickel ions; and providing a current to an anode plate and a cathode rotating drum spaced apart from each other in the electrolyte solution to provide a copper layer, and the concentration of the nickel ions is 50 ppm to 350 ppm.

[0013] The measured curl of the electrolytic copper foil is 12 mm or less.

[0014] The concentration of the nickel ions is 80 ppm to 280 ppm.

[0015] The measured curl of the electrolytic copper foil is 10 mm or less.

[0016] The density of the current supplied to the electrolyte is 4,500 A / m 2 ~6,500A / m 2 It is.

[0017] The concentration of the copper ions is 70 g / L to 100 g / L, and the concentration of the sulfuric acid is 80 g / L to 150 g / L.

[0018] In the step of preparing the electrolyte, an organic additive is added, and the organic additive includes at least one of an elongation modifier, a tensile strength modifier, and a gloss modifier.

[0019] The elongation modifier includes a nonionic water-soluble polymer, the tensile strength modifier includes at least one of a thiourea-based compound and a compound in which a thiol group is linked to a nitrogen-containing heterocycle, and the gloss modifier includes a sulfonic acid, which is a compound containing a sulfur atom, or a metal salt thereof.

[0020] The elongation modifier includes at least one of carboxymethyl cellulose, polyethylene glycol, hydroxyethyl cellulose (HEC), octanediol-bis-polyalkylene glycol ether, and polyglycerin.

[0021] The concentration of the elongation modifier is 1 ppm to 20 ppm.

[0022] The tensile strength modifier includes at least one of diethylthiourea, ethylenethiourea, acetylenethiourea, and 2-thiouracil.

[0023] The concentration of the tensile strength modifier is 5 ppm to 50 ppm.

[0024] The gloss control agent includes at least one of thiophosphoric acid-tris-(ω-sulfopropyl) ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS) and thioglycolic acid.

[0025] The gloss regulator has a concentration of 1 ppm to 30 ppm.

[0026] The thickness of the electrolytic copper foil is 10 μm or less. Effect of the Invention

[0027] According to the disclosed method for producing an electrolytic copper foil, the curling properties of the electrolytic copper foil can be improved by adding nickel ions together with copper ions to an electrolyte for producing the electrolytic copper foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;

[0029] To manufacture copper foil, first, copper (Cu) and nickel (Ni) are dissolved in sulfuric acid to prepare an electrolyte solution containing copper ions and nickel ions. The electrolyte solution is placed in an electrolytic cell.

[0030] Next, the anode plate and the cathode rotating drum, which were placed apart from each other in the electrolyte, were subjected to a current of 4,500 A / m 2 ~6,500A / m 2 A copper layer is formed by passing a current at a current density of 1000 .mu.m. The copper layer is formed by electroplating.

[0031] The copper layer thus produced is washed in a washing tank, and impurities on the surface of the copper layer are removed in the washing process. Next, the copper layer is immersed in an anti-rust solution in an anti-rust tank to form an anti-rust film on the copper layer. Copper foil is produced by forming the anti-rust film, and the copper foil is finally washed in a washing tank and dried, and then wound up by a winder to complete the copper foil manufacturing process. The copper foil manufacturing process may also be carried out through processes commonly used in other industries.

[0032] The electrolytic copper foil manufactured in the above manner is used for a negative electrode current collector of a secondary battery.

[0033] The electrolytic solution contains 70 g / L to 100 g / L of copper ions, 80 g / L to 150 g / L of sulfuric acid, and 50 ppm to 350 ppm of nickel ions, preferably 80 ppm to 280 ppm of nickel ions. Under the above-mentioned copper ion and sulfuric acid concentration conditions, a copper layer can be smoothly formed by electrodeposition of copper.

[0034] The organic additives contained in the electrolyte include at least one of an elongation modifier, a tensile strength modifier, and a gloss modifier.

[0035] The elongation adjuster includes a non-ionic water-soluble polymer. The elongation adjuster has a concentration of 1 ppm to 20 ppm in the electrolyte, and the elongation adjuster can contribute to maintaining and improving the elongation of the copper foil.

[0036] The elongation modifier includes at least one of carboxymethyl cellulose, polyethylene glycol, hydroxyethyl cellulose (HEC), octanediol-bis-polyalkylene glycol ether, and polyglycerin, but the type of the elongation modifier is not limited thereto, and other non-ionic water-soluble polymers that can be used in the manufacture of copper foils may be used as the elongation modifier.

[0037] The tensile strength modifier includes at least one of a thiourea compound and a compound in which a thiol group is linked to a nitrogen-containing heterocycle.

[0038] The tensile strength modifier has a concentration of 5 ppm to 50 ppm in the electrolyte, and the tensile strength modifier contributes to maintaining and improving the tensile strength of the copper foil.

[0039] The tensile strength modifier includes at least one of diethylthiourea, ethylenethiourea, acetylenethiourea, and 2-thiouracil.

[0040] The gloss regulator contains sulfonic acid, which is a compound containing a sulfur atom, or a metal salt thereof. The gloss regulator has a concentration of 1 ppm to 30 ppm in the electrolyte.

[0041] The gloss modifier increases the charge amount of the electrolyte, thereby increasing the copper electrodeposition rate and enhancing the gloss of the copper foil.

[0042] The gloss control agent includes at least one of thiophosphoric acid-tris-(ω-sulfopropyl) ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS) and thioglycolic acid.

[0043] Hereinafter, the present invention will be described in detail with reference to examples and comparative examples according to the present invention. However, the following examples and comparative examples are provided to facilitate understanding of the present invention, and the scope of the present invention is not limited by the examples or comparative examples. EXAMPLES

[0044] In Example 1, copper foil was manufactured using a foil-making machine including an electrolytic cell containing an electrolyte, and an anode plate and a cathode rotating drum spaced apart from each other in the electrolyte. The electrolyte was an electrolyte containing copper ions and nickel ions obtained by dissolving copper and nickel in sulfuric acid, and the concentration of copper ions in the electrolyte was 80 g / L, the concentration of sulfuric acid was 100 g / L, the concentration of elongation modifier (HEC, HydroxyEthyl Cellulose) was 10 ppm, the concentration of tensile strength modifier (Diethylthiourea) was 25 ppm, and the concentration of gloss modifier (SPS, Bis-(3-Sulfopropyl)-disulfide-disodium salt) was 15 ppm. The temperature of the electrolyte was set to 54° C., and the flow rate was set to 3,000 L / hr.

[0045] The nickel concentration in the electrolyte was adjusted by the amount of nickel sulfate added, as shown in Table 1 below. The copper foil was electrolyzed at 5,769 A / m 2 A current was supplied to the electrolytic cell by the constant current method at a current density of 1.0 μm, and the cathode rotating drum was rotated at a speed of 1.47 m / min to continuously produce electrolytic copper foils having a thickness of 8 μm. Copper foils of Invention Examples 1-1 to 1-13 and Comparative Examples 1-1 to 1-7 were produced according to the nickel concentration.

[0046] The copper foils manufactured in Examples 1-1 to 1-13 and Comparative Examples 1-1 to 1-7 were cut to a width of 10 cm and a length of 10 cm to prepare specimens. The specimens were placed on a flat floor, and the height at which the edge of the copper foil bent from the floor was measured and shown in Table 1.

[0047] [Table 1]

[0048] Referring to Table 1, the measured curl value of the copper foil produced in Comparative Example 1-1, in which nickel was not added to the electrolyte, was as high as 25.7 mm, while the measured curl value of the electrolytic copper foil produced in Examples 1-1 to 1-13, in which nickel ions were added to the electrolyte at a concentration of 50 ppm to 350 ppm, was suppressed to 12 mm or less. In addition, it can be confirmed that the measured curl value of the electrolytic copper foil was suppressed to 10 mm or less when the nickel ion concentration in the electrolyte was 80 ppm to 280 ppm as in Examples 1-2 to 1-10. When the electrolytic copper foil was produced, the residual stress inside the copper foil was reduced by adding an appropriate amount of nickel to the electrolyte, and thus the measured curl value of the electrolytic copper foil was reduced. It should be understood that when the measured curl value of the copper foil produced is generally 12 mm or less, the curl property is excellent, and when the measured curl value is 10 mm or less, the curl property is very excellent.

[0049] It can be seen that the electrolytic copper foils manufactured under the condition of nickel concentration in the electrolyte of 50 ppm or less as in Comparative Examples 1-2 and 1-3 suppress the occurrence of curling compared to Comparative Example 1-1 in which no nickel was added, but the effect is not significant.

[0050] It was confirmed that the curl suppression effect was reduced again in the electrolytic copper foils manufactured in Comparative Examples 1-4 to 1-7, in which the nickel concentration in the electrolyte exceeded 350 ppm. This is understood to be because when the nickel concentration in the electrolyte exceeds a certain range, the uniform growth of copper particles is hindered, thereby reducing the curl suppression effect.

[0051] Therefore, by adjusting the nickel concentration in the electrolyte for producing electrolytic copper foil to 50 ppm to 350 ppm, preferably 80 ppm to 280 ppm, it is possible to produce electrolytic copper foil with improved curl properties. EXAMPLES

[0052] In Example 2, an electrolytic copper foil was produced under the same conditions as in Example 1, except that the copper ion concentration, sulfuric acid concentration, and nickel ion concentration in the electrolyte of Example 1 were changed as shown in Table 2.

[0053] The copper foils manufactured in Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4 were cut into specimens with a width of 10 cm and a length of 10 cm. The specimens were placed on a flat floor, and the height at which the edge of the copper foil bent from the floor was measured and shown in Table 2.

[0054] [Table 2]

[0055] Referring to Table 2, it can be seen that the measured curl of the electrolytic copper foils manufactured according to Examples 2-1 to 2-6, in which the nickel ion concentration in the electrolyte containing copper ions and nickel ions is 50 ppm to 350 ppm, is suppressed to 12 mm or less even when the copper ion concentration and sulfuric acid concentration change within a certain range. On the other hand, it can be seen that when the nickel ion concentration is out of the range of 50 ppm to 350 ppm (Comparative Examples 2-1 to 2-4), the curl amount exceeds 12 mm. Also, as confirmed in Example 1, when the nickel ion concentration is 80 ppm to 280 ppm, that is, in the cases of Examples 2-2, 2-3, and 2-4 of Example 2, it can be seen that the measured curl of the electrolytic copper foils is suppressed to 10 mm or less.

[0056] Therefore, by adjusting the nickel concentration in the electrolyte for producing electrolytic copper foil to 50 ppm to 350 ppm, preferably 80 ppm to 280 ppm, it is possible to produce electrolytic copper foil with improved curl properties. EXAMPLES

[0057] In Example 3, an electrodeposited copper foil was produced under the same conditions as in Example 1, except that the concentrations of the elongation modifier (HEC, HydroxyEthyl Cellulose), the tensile strength modifier (Diethylthiourea), the gloss modifier (SPS, Bis-(3-Sulfopropyl)-disulfide-disodium) and nickel ions in the electrolyte solution of Example 1 were changed as shown in Table 3.

[0058] The copper foils manufactured in Examples 3-1 to 3-8 and Comparative Examples 3-1 to 3-4 were cut into specimens with a width of 10 cm and a length of 10 cm. The specimens were placed on a flat floor, and the height at which the edge of the copper foil bent from the floor was measured and shown in Table 3.

[0059] [Table 3]

[0060] Referring to Table 3, it can be seen that the measured curl of the electrolytic copper foils manufactured according to Examples 3-1 to 3-8, in which the nickel ion concentration in the electrolyte was 50 ppm to 350 ppm, was suppressed to 12 mm or less even if the concentrations of the elongation modifier (HEC, HydroxyEthyl Cellulose), tensile strength modifier (Diethylthiourea), and gloss modifier (SPS, Bis-(3-Sulfopropyl)-disulfide-disodium) were changed within a certain range. On the other hand, when the nickel ion concentration was out of the range of 50 ppm to 350 ppm (Comparative Examples 3-1 to 3-4), it was seen that the curl amount exceeded 12 mm.

[0061] In addition, as confirmed in Example 1, when the nickel ion concentration is 80 ppm to 280 ppm, i.e., in the cases of Invention Examples 3-2, 3-3, and 3-4 of Example 3, it can be confirmed that the measured curl value of the electrolytic copper foil is suppressed to 10 mm or less.

[0062] Therefore, by adjusting the nickel concentration in the electrolyte for producing electrolytic copper foil to 50 ppm to 350 ppm, preferably 80 ppm to 280 ppm, it is possible to produce electrolytic copper foil with improved curl properties.

[0063] According to the examples of the present invention, curling that may occur during the manufacturing process of the electrolytic copper foil can be prevented, thereby preventing breakage of the electrolytic copper foil.

[0064] Although the present invention has been described herein with reference to certain embodiments, it should be understood that various modifications and variations may be made without departing from the spirit and scope of the present invention as would be understood by one of ordinary skill in the art to which the present invention pertains, and such modifications and variations are to be considered as falling within the scope of the claims appended hereto.

Claims

1. In the method for producing an electrolytic copper foil, Dissolving copper (Cu) and nickel (Ni) in sulfuric acid to prepare an electrolyte solution containing copper ions and nickel ions; and providing a copper layer by supplying an electric current to an anode plate and a cathode rotating drum spaced apart from each other in the electrolyte; The concentration of the nickel ions is 50 ppm to 350 ppm; The concentration of the copper ions is 70 g / L to 100 g / L; The concentration of the sulfuric acid is 80 g / L to 150 g / L, the density of the current supplied to the electrolyte is 4,500 A / m 2 to 6,500 A / m 2 ; The method for producing an electrolytic copper foil, wherein the measured curl of the electrolytic copper foil is 12 mm or less.

2. The method for producing an electrolytic copper foil according to claim 1, wherein the concentration of the nickel ions is 80 ppm to 280 ppm.

3. The method for producing an electrolytic copper foil according to claim 2, wherein the measured curl of the electrolytic copper foil is 10 mm or less.

4. In the step of preparing the electrolyte, an organic additive is further added, The organic additive includes at least one of an elongation modifier, a tensile strength modifier, and a gloss modifier; The elongation modifier includes at least one of carboxymethyl cellulose, polyethylene glycol, hydroxyethyl cellulose (HEC), octanediol-bis-polyalkylene glycol ether, and polyglycerin; The tensile strength modifier includes at least one of a thiourea compound and a compound having a thiol group linked to a nitrogen-containing heterocycle, The method for producing an electrolytic copper foil according to any one of claims 1 to 3, wherein the gloss regulator contains a sulfonic acid or a metal salt thereof, which is a compound containing a sulfur atom.

5. The method for producing an electrolytic copper foil according to claim 4, wherein the concentration of the elongation adjuster is 1 ppm to 20 ppm.

6. The method for producing an electrolytic copper foil according to claim 4, wherein the tensile strength modifier comprises at least one of diethylthiourea, ethylenethiourea, acetylenethiourea, and 2-thiouracil.

7. The method for producing an electrolytic copper foil according to claim 6, wherein the concentration of the tensile strength modifier is 5 ppm to 50 ppm.

8. 5. The method for producing an electrolytic copper foil according to claim 4, wherein the gloss control agent comprises at least one of thiophosphoric acid-tris-(ω-sulfopropyl) ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS) and thioglycolic acid.

9. The method for producing an electrolytic copper foil according to claim 8, wherein the concentration of the gloss adjuster is 1 ppm to 30 ppm.

10. The method for producing an electrolytic copper foil according to any one of claims 1 to 3, wherein the thickness of the electrolytic copper foil is 10 µm or less.

Citation Information

Patent Citations

  • Copper foil electrolyte, copper foil production method and copper foil electrolysis equipment

    CN106968000A

  • Copper-nickel alloy foil and electro-deposition preparation method thereof

    CN111321437A

  • Electrolytic copper foil and method for manufacturing the same

    JP2001123290A

  • Copper electrolyte

    JP2012211369A

  • Copper foil for current collector of lithium secondary battery

    JP2019099911A